2008
DOI: 10.1007/s10493-008-9172-8
|View full text |Cite
|
Sign up to set email alerts
|

Sprays of emulsifiable Beauveria bassiana formulation are ovicidal towards Tetranychus urticae (Acari: Tetranychidae) at various regimes of temperature and humidity

Abstract: Aerial conidia of Beauveria bassiana in an emulsifiable formulation germinated by >95% after 24 h exposure to the regimes of 20, 25 and 30 degrees C with 51%, 74% and 95% RH. Ovicidal activities of the formulation towards two-spotted spider mite, Tetranychus urticae, were assayed at the concentrations of 0, 18, 160 and 693 conidia mm(-2) sprayed separately onto fava bean leaves including 39 (25-76) eggs per capita. All the sprayed eggs on the leaves were directly exposed to the different regimes for hatch afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…The mean (±SD) concentration of conidia deposited onto the leaves was 1.13 (±0.14) 9 10 3 , 1.55 (±.22) 9 10 3 and 0.95 (±0.26) 9 10 3 conidia mm -2 for the three isolates, respectively. These estimates were based on five microscopic counts from each of glass cover slips (20 9 20 mm) that had been placed beside the leaf dish to collect deposited conidia during spraying (Shi et al 2008c). …”
Section: Fecundity Assaysmentioning
confidence: 99%
“…The mean (±SD) concentration of conidia deposited onto the leaves was 1.13 (±0.14) 9 10 3 , 1.55 (±.22) 9 10 3 and 0.95 (±0.26) 9 10 3 conidia mm -2 for the three isolates, respectively. These estimates were based on five microscopic counts from each of glass cover slips (20 9 20 mm) that had been placed beside the leaf dish to collect deposited conidia during spraying (Shi et al 2008c). …”
Section: Fecundity Assaysmentioning
confidence: 99%
“…Since the 1960s, more than 150 insect biocontrol products based on fungal entomopathogens, including I. fumosorosea , have been commercially available all over the world . A substantial number of mycoinsecticides have been widely used for biological control of insect pests . However, these fungal products make up a small percentage of the total insecticide market, owing largely to their slower insecticidal activity compared with insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate efficacy of SD-tower sprayer, we compared the deposited conidia rates with previously reported results using potter tower sprayer in bioassay (Vicentini et al, 2001;Tian et al, 2006;Shapiro-Ila et al, 2008;Shi et al, 2008;Shan et al, 2010;) (Table 1). The result showed that SD-tower sprayer was superior to other sprayers with 0.58% rate of deposited conidia per cm 2 .…”
Section: Resultsmentioning
confidence: 99%